Impact of Genetic Variation in TLR4 3′UTR on NSCLC Genetic Susceptibility - Hongjiao Wu (Journal of Oncology, 2020)
Toll-like receptors (TLRs) are expressed not only in immune cells but also in a variety of tumor cells. Single-nucleotide polymorphisms (SNPs) located in the TLRs’ promoter or the 3′ untranslated region may affect gene expression by affecting the activity of the promoter or regulating the binding of mRNA to miRNA. This study aimed to investigate the association of the SNPs in TLR genes with the susceptibility to NSCLC. This case-control study involved 700 lung cancer patients and 700 healthy controls. All individuals were genotyped for all selected SNPs in TLR genes using polymerase chain reaction (PCR) test-based restriction fragment length polymorphism (PCR-RFLP) and TaqMan SNP genotyping assay. The association of genetic variations in TLRs with the susceptibility to NSCLC was evaluated by unconditional logistic regression with OR (95% CI). After evaluating transcriptional factor or miRNA binding capability by bioinformatics methods, six TLRs were identified for further analysis. We did not find that TLR3 rs5743303, TLR4 rs1927914, TLR4 rs11536891, TLR5 rs1640816, and TLR7 rs3853839 were associated with NSCLC risk (P>0.05). Our data showed that TLR4 rs7869402 C > T polymorphism reduced the risk of NSCLC with OR (95% CI) of 0.63 (0.45–0.89). When stratified by gender and age, the individuals carrying at least one rs7869402T allele significantly decreased the NSCLC risk among males (OR = 0.58, 95% CI = 0.38–0.87) and among youngsters (OR = 0.43, 95% CI = 0.27–0.69). Smoking stratification analysis showed that the rs7869402T allele-containing genotype reduced the risk of NSCLC with OR (95% CI) of 0.50 (0.29–0.87) among smokers but not among nonsmokers (P>0.05). When the individuals were classed by the pathological type, we found that the rs7869402T-containing genotype was associated with the risk of adenocarcinoma (OR = 0.62, 95% CI = 0.41–0.92) but not with that of squamous cell carcinoma (OR = 0.71, 95% CI = 0.44–1.13) and other types (OR = 0.23, 95% CI = 0.03–1.70). Compared with the TLR4 Ars1927914-Crs7869402-Trs11536891 haplotype, the Grs1927914-Trs7869402-Trs11536891 haplotype was associated with a decreased risk for developing NSCLC with OR (95% CI) of 0.57 (0.41–0.80). These results indicated that the TLR4 rs7869402 variation affects the genetic susceptibility to NSCLC.